Stalinowska konstytucja z 1936 r. i nadzieje wierzących na Sowieckiej Ukrainie na zmianę antyreligijnej polityki bolszewików - Kuśnierz, Robert (Archiwa, Biblioteki i Muzea Kościelne, 2017)
This article discusses Ukrainians’ hope for a change of the anti-religious Bolshevik policy after the adoption of the Stalin Constitution in 1936. Article 124 of the constitution encouraged the faithful to ask for reactivating closed churches, releasing arrested priests and allowing priests to conduct their duties. However, the constitution did not lead to any improvement in the life of the faithful. The Bolsheviks adopted "the most democratic constitution in the world," but they interpreted liberties it contained in their own way.